Organizational Climate and Support Can Enhance Knowledge Sharing (Study of Private University Lecturers in Indonesia) - Putri, RatnaKomala (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine and analyze the influence of organizational climate and support on knowledge sharing at private universities in West Java. In the present study, the respondents consist of 275 lecturers, 273 respondents from 15 accredited private universities in West Java. The male respondents constitute 34.3%, while 65.7% of them are female. The study used the quantitative method, and the structural equation model (SEM) was used as an analysis tool. A study on organizational climate associated with organizational support and knowledge sharing at a private university has never been conducted by previous researchers; thus, the current research has a high originality. As such, this research can contribute to enhancing knowledge sharing in private universities. A conducive organizational climate and optimum support of the organization encourage knowledge sharing at private universities.